2004
DOI: 10.1038/sj.onc.1207955
|View full text |Cite
|
Sign up to set email alerts
|

Regulated proteolysis of the IFNaR2 subunit of the interferon-alpha receptor

Abstract: The type I interferons (IFNs) bind surface receptors, induce JAK kinases and activate STAT transcription factors to stimulate the transcription of genes downstream of IFN-stimulated response elements (ISREs). In this study, we demonstrate that IFNaR2, a subunit of the type I IFN receptor, is proteolytically cleaved in a regulated manner. Immunoblotting shows that multi-step cleavage occurs in response to phorbol ester (PMA) and IFN-a, generating both a transmembrane 'stub' and the intracellular domain (ICD), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…While investigating the canonical JAK-STAT pathway for IFN signaling [25,33], we demonstrated that i) Stat2 can bind IFNaR2 constitutively; ii) this binding is s t r o n g e r t h a n t h e b i n d i n g o f phosphorylated-IFNaR1 to Stat2 that occurs following IFN-driven receptor dimerization; and iii) the IFNaR2-Stat2 interaction is not required for canonical JAK-STAT signaling/gene regulation. These findings suggested that IFNaR2 might signal by other, non-canonical mechanisms and, indeed, we subsequently found that this subunit of the IFN receptor is proteolytically cleaved in a regulated manner that resembles signaling by other RIP substrates [21]. We also showed that the receptor ICD can modulate transcription via the TAD of the bound Stat2 molecule [22].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While investigating the canonical JAK-STAT pathway for IFN signaling [25,33], we demonstrated that i) Stat2 can bind IFNaR2 constitutively; ii) this binding is s t r o n g e r t h a n t h e b i n d i n g o f phosphorylated-IFNaR1 to Stat2 that occurs following IFN-driven receptor dimerization; and iii) the IFNaR2-Stat2 interaction is not required for canonical JAK-STAT signaling/gene regulation. These findings suggested that IFNaR2 might signal by other, non-canonical mechanisms and, indeed, we subsequently found that this subunit of the IFN receptor is proteolytically cleaved in a regulated manner that resembles signaling by other RIP substrates [21]. We also showed that the receptor ICD can modulate transcription via the TAD of the bound Stat2 molecule [22].…”
Section: Discussionmentioning
confidence: 52%
“…and J.J.K.). The stub is subsequently cleaved in a constitutive manner by the g -secretase protease complex, containing PS1 and PS2 [21].…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we employed a construct in which GFP is fused to the IFNaR2-ICD, and a cell line (U6A) deficient in the expression of Stat2. Previously, we have shown that following transient transfection, GFP-ICD localized to the nucleus of U2OS cells [21]. In contrast, in U6A cells, GFP-ICD was predominantly cytoplasmic (Fig.…”
Section: Stat2 Is Required For Ifnar2-icd Nuclear Importmentioning
confidence: 99%
“…We have recently found that phorbol ester and type I IFNs induce proteolytic cleavage of the IFNaR2 receptor subunit in a manner that resembles the two-step RIP cleavage of Notch [21]. Subsequently, we demonstrated that the intracellular domain of IFNaR2 (IFNaR2-ICD) can mediate gene transcription in a Stat2 dependent manner [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation